2022
DOI: 10.1287/mksc.2021.1321
|View full text |Cite
|
Sign up to set email alerts
|

Frontiers: Virus Shook the Streaming Star: Estimating the COVID-19 Impact on Music Consumption

Abstract: How has the COVID-19 pandemic affected the consumption of audio music streaming?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 12 publications
0
20
1
Order By: Relevance
“…We recognise that other types of arts engagement activities may exhibit a different trend over time. For instance, an analysis of Spotify’s streaming data in 60 countries has showed a notable reduction in music streaming during the COVID-19 outbreak, 31 in contrast to the surge in arts and crafts sales. 6 Therefore, future studies could extend our analyses by including other types of home-based arts engagement activities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We recognise that other types of arts engagement activities may exhibit a different trend over time. For instance, an analysis of Spotify’s streaming data in 60 countries has showed a notable reduction in music streaming during the COVID-19 outbreak, 31 in contrast to the surge in arts and crafts sales. 6 Therefore, future studies could extend our analyses by including other types of home-based arts engagement activities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This inherent timeliness of web data continues to be an essential lever for marketing scholars to advance our understanding of emerging substantive topics such as the sharing economy (e.g., Airbnb; Zervas, Proserpio, and Byers 2017), access-based business models (e.g., Spotify; Datta, Knox, and Bronnenberg 2018), and fake online content (e.g., Anderson and Simester 2014). More generally, web data enable researchers to weigh in on contemporary issues before any “conventional” data sets become available, such as measuring the effect of pandemic lockdown policies on consumption (Sim et al 2022).…”
Section: Using Web Data To Advance Marketing Thoughtmentioning
confidence: 99%
“…While Mak et al and Hurwitz and Krumhansl did not find self-reported increases in musical engagement (for UK and US samples), other studies reported higher levels of daily musical engagement or an increased importance of music ( Cabedo-Mas et al , Carlson et al , Ferreri et al , Ribeiro , Janzen et al ). Quantitative reports of decreased audio streaming (e.g., Spotify) accompanied by increased video streaming (e.g., YouTube) of music during lockdown (Sim et al, 2020 ; see also Carlson et al ) point toward a possibly accelerated uptake of multimodal media for music consumption and potentially inaccurate introspections about actual use (Hansen, in press B ).…”
Section: Overview Of Contributionsmentioning
confidence: 99%